THE WAY TO THE HUMAN HEART BEGINS WITH KINDNESS AND GENEROSITY - Badalbaeva Irodakhon Khabibulaevna (Zeta Repository, 2023)
Kindness and doing good is a means of increasing people's mutual love and sincerity. These aspects are emphasized in religious and philosophical sources. This article will discuss this issue.